Effects of platelet-rich plasma in a model of bovine endometrial inflammation in vitro - Marini, Maria Giovanna (Reprod Biol Endocrinol, 2016)
BACKGROUND: Endometritis reduces fertility and is responsible for major economic losses in beef and dairy industries. The aim of this study was to evaluate an alternative therapy using platelet-rich plasma (PRP). PRP was tested in vivo, after bovine intrauterine administration, and in vitro on endometrial cells. METHODS: Bovine endometrial cells were cultured until passage (P) 10 with 5 % or 10 % PRP. Effect of PRP on endometrial cell proliferation and on the expression of genes [prostaglandin-endoperoxide synthase 2 (COX2), tumor protein p53 (TP53), oestrogen receptors (ER-α and ER-β), progesterone receptor (PR) and c-Myc] involved in the regulation of oestrus cycle and fetal-maternal interaction were evaluated. Moreover, to evaluate the ability of PRP to counteract inflammation, 10 and 100 ng/ml of bacterial endotoxin lipopolysaccharide (LPS) were used to inflame endometrial cells in vitro for 1, 6, 12, 24 and 48 h. The expression of genes such as interleukin 1β (IL-1β), interleukin-8 (IL-8), inducible nitric oxide synthase (iNOS), prostaglandin-endoperoxide synthase 2 (COX2/PTGS2), and the release of PGE-2, IL-1β and IL-8 were evaluated. RESULTS: In vivo treatment with PRP increased the detection of PR. In vitro, 5 % PRP at passage 5 increased proliferation rate and induced a significant increase in the expression of all studied genes. Furthermore, the results revealed that 10 ng/ml of LPS is the most effective dose to obtain an inflammatory response, and that PRP treatment significantly down regulated the expression of pro-inflammatory genes. CONCLUSION: This study lays the foundations for the potential treatment of endometritis with PRP in vivo.